Advanced IoT-integrated real-time fire detection and automated mitigation system - Rama Krishna Peddarapu; Ajimera Abhinav; Gnana Sathwika V. N. V.; Poosa Brijesh; Amrutha Varshini Ravula (International Journal of Informatics and Communication Technology (IJ-ICT), 2026)
In the field of industry and commerce safety, tackling the most challenging and ongoing fire threats requires the advance internet of things (IoT) integrated real-time fire detection and automated mitigation system. Leveraging IoT and multi-modal sensing in fire safety, the system combines flame, gas, and humidity sensors and cameras to provide continuous real time monitoring and appropriate management of the threats. Real-time automated hazard interventions, such as sprinkler system engagement and geocoded alerts to fire departments, significantly improve life safety outcomes of the system. Active damage mitigation IoT devices provide integrated damage mitigation safety and individual IoT device remote monitoring. In the scope of industry and commerce, this system is a demonstration of the impact of IoT on improving fire safety.